From Tehran to the World Stage: The Inspiring Mathematical Legacy of Maryam Mirzakhani (1977-2017) - Koley, Susanta; Sen, Bimal Kanti (Information Research Communications, 2026)
Aim This study analyzes 35 publications by Maryam Mirzakhani from 1995 to 2016, focusing on her research output and collaboration with 20 co-authors. Background Maryam Mirzakhani was an outstanding Iranian mathematician and the first woman to win the “Fields Medal’’. This award is one of the highest honors in mathematics and is often compared to the “Nobel Prize”. Results She has authored a total of 35 publications, including 15 single-authored and 20 co-authored works. Her research career began early, with her first paper published in 1995 at the age of 18. Her most productive period was between 2010 and 2014, during which she published approximately three papers per year while aged 33 to 37. Notably, her productivity coefficient peaked at 1.0 in the years 1999, 2009, 2011–2012, and 2014–2015. Among her collaborators, A Eskin was the most active or core collaborators. She used 26 communication channels to disseminate the results of her research of which arXiv preprintar Xiv (a preprint server) (6 papers) top of the list followed by Annals of Mathematics (2), International Mathematics Research Notices (2), Inventiones Mathematicae (2), and Journal of Modern Dynamics (2). Her publication concentration is measured at 53.85, with a publication density of 1.35. The most commonly used keywords in her research are “Moduli space” (appearing nine times) and “Hyperbolic surfaces” (six times), reflecting her primary areas of scholarly focus. Conclusion Her achievement made history and inspired many people around the world, especially women, to study mathematics. Her untimely demise is a universal loss in mathematical research.
Keywords: Field Medal; Fields Medalist; Geometry and Dynamical Systems; Iranian Mathematician; Maryam Mirzakhani; Mathematics; Moduli spaces; Nobel Prize; Riemann surfaces.